Self-Acceptance and Resilience among People Living with HIV in a Community-Based Setting in Makassar - Musfirah; Alamsyah Alamsyah; Ratna Wulandari (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2026)
Previous studies on resilience among People Living with HIV (PLHIV) have predominantly emphasized individual psychological factors, while the role of community-based accompaniment contexts remains underexplored. Addressing this gap, this study examined the relationship between self-acceptance and resilience among PLHIV assisted by a community-based organization in Makassar. This quantitative research employed a correlational design involving 53 PLHIV affiliated with Yayasan Gaya Celebes. Data were collected using validated self-acceptance and resilience questionnaires and analyzed through descriptive statistics, assumption testing, and Pearson Product Moment correlation analysis. The findings indicated that most participants demonstrated moderate levels of both self-acceptance and resilience. Although a positive association was observed between self-acceptance and resilience (r = 0.251), the relationship did not reach statistical significance (p > 0.05), and the effect size was small. These results suggest that self-acceptance may function as a supportive psychological resource rather than a primary determinant of resilience within a community-assisted context. Theoretically, this study contributes to the multidimensional understanding of resilience by demonstrating that internal psychological factors alone may not sufficiently explain adaptive functioning among PLHIV. The findings reinforce the importance of situating resilience within broader social and contextual frameworks. Practically, the study underscores the relevance of strengthening community-based accompaniment programs through peer support, stigma reduction initiatives, and sustained psychosocial assistance embedded in local contexts.